A phase Ⅱ, randomized, controlled trial to evaluate the safety and immunogenicity of a Sabin strain-based inactivated polio vaccine - Rong Tang; Guifan Li; Chengfu Zhang; Hengkui Zhi; Jiahong Zhu; Jianjun Wang; Qi Liang; Yuemei Hu; Changgui Li (Taylor & Francis Group, 2020)
This phase Ⅱ, randomized, controlled trial aimed to evaluate the safety and immunogenicity of a various Sabin IPV preparations. Six hundred infants aged 60 ~ 90 days received one of five different vaccines: low- (group A), medium- (group B) or high-D antigen content (group C) of an experimental Sabin IPV, control Sabin IPV (group D) or control Salk IPV (group E), on a 0-1-2 month schedule. Participants were observed and followed up within 30 days of each dose to assess safety. Serum samples were collected before the first dose and 30 days after the third dose to assess immunogenicity. After three doses, type-1 seroconversion rates of groups A-E were 99.1%, 100.0%, 99.1%, 99.0%, and 93.4%, respectively; type-2 seroconversion rates were 93.5%, 97.1%, 98.1%, 95.1%, and 91.5%, respectively; and type-3 seroconversion rates were 95.4%, 98.1%, 98.1%, 95.1%, and 100.0%, respectively. Only type-1 seroconversion rates differed significantly for group E. The incidences of injection-site redness (A: 21.9%, B: 23.7%, C: 29.4%, D: 16.2%, E: 12.7%), swelling (A: 6.7%, B: 6.8%, C: 5.0%, D: 0.0%, E: 1.7%) and pain (A: 5.0%, B: 6.8%, C: 7.6%, D: 0.0%, E: 0.9%) all were significantly higher for experimental vaccines relative to control groups. No SAEs were detected related to vaccination, and most adverse reactions were mild or moderate in severity. In conclusion, the experimental Sabin IPVs with low-, medium-, and high-D antigen content all revealed good safety and immunogenicity profiles although being more reactogenic than the control vaccines.